Memetakan Anatomi Diskursus Islamisme dan Terorisme Islam - Ridwan Rosdiawan (Islamica: Jurnal Studi Keislaman, 2018)
Abstract: What is the main factor of terrorism; Islamic doctrine, or political factor? There are three mainstream opinions provide theoretical reviews. Firstly, those who believe that the justification of acts of violence to terrorism is an inherent product of religious doctrine. Secondly, those who consider that terrorism is a profane matter have absolutely nothing to do with religion. Thirdly, the opinion which states that terrorism is syncretism and interrelated modification between politics and religion. This article tries to examine the three views above by dissecting other perspectives in order to get a clearer picture of the discourse of Islamism transforming into a radical movement leading to terrorism. Doctrinal and political motives are so strongly integrated and overlapping in the structure of the motives and actions of these radical groups. Departing from the view that Islamism is a movement that aims to make radical-revolutionary changes in social structure institutions, this article collects theories that can be used as maps to understand the construction of Islamism.